ANEMIA AMONG ADOLESCENT GIRLS: A GLOBAL REVIEW OF PREVALENCE, RISK FACTORS, AND INTERVENTIONS - Fitariani, Selvia; Masruroh; Mawarti, Herin; Nasrudin (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Anemia remains a significant public health challenge affecting adolescent girls worldwide, particularly in low- and middle-income countries (LMICs). This condition undermines growth, cognitive development, school performance, and reproductive health, with long-term intergenerational consequences. Objective: This systematic review aimed to systematically review the global prevalence, associated risk factors, and intervention strategies targeting anemia among adolescent girls, and to identify research and policy gaps that hinder effective prevention. Design: A systematic review of quantitative and mixed-methods studies conducted between January 2019 and May 2024 was undertaken by the PRISMA guidelines. Data Sources: Five electronic databases (PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar) were searched using Boolean combinations of keywords such as